2023
DOI: 10.1101/2023.09.18.558226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal Coordination of Active Deformation Forces and Wnt / Hippo-Yap Signaling inHydraRegeneration

Ryo Suzuki,
Tetsuya Hiraiwa,
Anja Tursch
et al.

Abstract: Ample evidence suggests that Wnt signaling and tissue deformation are key determinants for pattern formation in animals. The coordination of these biochemical and biomechanical spatio temporal asymmetries is often unknown or controversial. We investigated this relationship by studying regeneration in the freshwater polyp Hydra. In both reaggregates of dissociated cells and tissue regenerates we found significant tissue contraction waves and upregulation of Wnt signaling. Applying a simple mechanical model to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…How the mechanical role of actin topological defects is coupled to the Wnt organizer remains to be explored. However, recent findings propose that stretching of cells associated with larger stresses at the defects may be coupled to Wnt production through mechano-sensing signalling 22 in line with past findings suggesting a tight coupling mechanochemical coupling in the animal 8,9,23 .…”
Section: Text: 2998 Wordssupporting
confidence: 77%
“…How the mechanical role of actin topological defects is coupled to the Wnt organizer remains to be explored. However, recent findings propose that stretching of cells associated with larger stresses at the defects may be coupled to Wnt production through mechano-sensing signalling 22 in line with past findings suggesting a tight coupling mechanochemical coupling in the animal 8,9,23 .…”
Section: Text: 2998 Wordssupporting
confidence: 77%
“…In this work, the simplified Schnakenberg model is used to describe the upstream biochemical signaling network. It is imperative to recognize that the intracellular signaling pathways [e.g., multitiered reaction networks ( 43 , 72 )] and their intercellular propagation [e.g., directional distributions influenced by tissue polarity ( 23 , 73 )] exhibit a level of intricacy beyond the scope of the Schnakenberg model. For the mechanical components, the way how cells contract or are stretched varies across different systems, encompassing the behaviors such as overall volume change ( 61 ), the maintenance of nearly constant volume ( 18 ), or deformations of the basal surface ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of intercellular wave patterns, both temporal and spatial, have been identified in multicellular systems spanning various biochemical intricacies ( 13 , 18 23 ). In morphogenesis of murine cochlear duct, extracellular signal–regulated kinase (ERK) activation waves have been found to control cell migration and result in the duct elongation ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, local activation of Wnt can promote head organizer formation (Wang et al, 2020) and global Wnt activation results in a multi-headed phenotype (Broun et al, 2005;Ferenc et al, 2021). More recent work revealed that the Hippo-YAP pathway is also involved in axial patterning in Hydra, during budding (Broun et al, 2022) and regeneration from tissue segments and aggregates (Suzuki et al, 2023). Despite this progress, axial patterning in Hydra is still not well understood (Holstein, 2022).…”
Section: Introductionmentioning
confidence: 99%